1970
DOI: 10.3329/sjps.v1i1.1809
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Nitric Oxide Scavenging Activity of Ethanol Leaf Extracts of Four Bangladeshi Medicinal Plants

Abstract: The ethanol leaf extracts of four medicinal plants named Hibiscus mutabilis, Leucas aspera, Ixora coccinea and Polyalthia longifolia were examined for their possible regulatory effect on nitric oxide (NO) levels using sodium nitroprusside as a NO donor in vitro. Most of the extracts tested demonstrated direct scavenging of NO and exhibited significant activity and the potency of scavenging activity was in the following order: Leucas aspera > Ixora coccinea > Hibiscus mutabilis> Polyalthia longifolia. All the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These compounds are responsible for altering the structural and functional behavior of many cellular components. [ 26 ] Nitric oxide produced by SNP over 2-hour incubation at 25°C has been scavenged by the decoction. The decoction used in the present study contains strong nitric oxide scavenging activity with an EC 50 of 14.02 ± 0.66 μg/ml as compared with Pyrus boissieriana , Cnidium officinale , and Ligusticum chuanxiong , which showed an EC50 of 650, 57.25, and 76.50 μg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are responsible for altering the structural and functional behavior of many cellular components. [ 26 ] Nitric oxide produced by SNP over 2-hour incubation at 25°C has been scavenged by the decoction. The decoction used in the present study contains strong nitric oxide scavenging activity with an EC 50 of 14.02 ± 0.66 μg/ml as compared with Pyrus boissieriana , Cnidium officinale , and Ligusticum chuanxiong , which showed an EC50 of 650, 57.25, and 76.50 μg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This activity may allow P. aeruginosa an advantage over competing bacteria occupying the same niche. Furthermore, pyocyanin has a variety of pharmacological effects on eukaryotic and prokaryotic cells [5]. [6,7] indicated that pyocyanin has antimicrobial activity against bacteria, fungi, and protozoa, but it is little therapeutic value because it is quite toxic to eucaryotic cells, since pyocyanin inhibited mammalian cell respiration disrupt the beating of human cilia, and inhibit both epidermal cell growth and lymphocyte proliferation.…”
Section: Antibiotic Action Of Pyocyaninmentioning
confidence: 99%
“…Results from present study suggested that 16-hydroxycleroda-3,13-dien-15,16-olide (23) and 16-oxocleroda-3,13-dien-15-oic acid (24) (Figure 1 ) has significantly ( P < 0.05) reduced NO production at 10 μg/mL, with 81.1 and 86.3%, inhibition, respectively. Similarly, Saha et al ( 2008 ) conducted a study on Bangladeshi medicinal Plants ( Hibiscus mutabilis, Leucas aspera, Ixora coccinea , and P. longifolia) . Ethanolic extract of all the tested species showed dose dependent NO direct scavenging activity in following manner L. aspera > I. coccinea > H. mutabilis > P. longifolia .…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%